Pemanfaatan Limbah Rumah Tangga dan Pemberdayaan Remaja Untuk Peningkatan Pendapatan Rumah Tangga Di Desa Blang Pulo Kecamatan Muara Satu Kota Lhokseumawe - Devi Andriyani; Ratna Ratna; Ichsan Ichsan; Yurina Yurina; Hijri Juliansyah (Universitas Malikussaleh, 2023)
One of the causes of the high unemployment rate in Indonesia, especially Aceh, is the low public awareness of the available potential and this condition is exacerbated by the weak spirit of youth entrepreneurship. This service aims to empower youth's spare time by utilizing household waste to increase family income, foster a culture of entrepreneurship, independence and develop handicraft-based MSMEs, in Blang Pulo Village, Muara Satu District, Lhokseumawe City. The service implementation method is carried out with 3 main steps, namely the awareness stage, the training stage, and the supervision stage from the service team on partner skills. As for the results of this service, 90% of partners have understood the material presented and shown a positive impact in the form of changing mindsets and raising awareness of the need for partners to use free time for positive activities and generate income. At the capacity building stage, 85% of the partners mastered craft materials to turn household waste into goods of economic value. Meanwhile, at the awareness stage, the influence felt by partners is also very good and positive, it is shown that there is a continuation of activities with the formation of MSMEs established by partners by utilizing waste.